Some applications of biotechnology in nutrition of ruminants (Agroindustria, Sociedad y Ambiente, 2020)
In the field of ruminant nutrition, biotechnology offers tools from different sources and diverse applications, including: genetic intervention of plants, genetic modification of microorganisms, products based on beneficial microorganisms, complexes of fibrolytic enzymes, and bio processes -conversion. The application of biotechnological tools is useful for improving the nutritional value of fodder and other foods, health and animal performance, as well as providing benefits for the environment, provided that use with awareness, ethics and rationality is promoted. This document describes some of the biotechnological techniques or practices of greater use or potential application in ruminant nutrition.
Keywords: Biotechnology; nutrition; ruminants